The securitisation of ethnic identities and the 1993 genocide in Burundi: an interpretative case study - Goll, Anna Lena (Department of Political Studies, 2022)
This dissertation investigates the 1993 Genocide of Burundi's Hutu and Tutsi population as the product of the securitisation of ethnic identities. By utilising an International Security Studies approach in combination with a Fanonian conception of colonial society, this dissertation provides an alternative interpretation as to why the genocide occurred. At heart of its analysis is the question of ‘how did ethnic identities in Burundi become securitised?', which it seeks to answer through a qualitative research design based on the interpretative case study method. By reconstructing particular representations of enmity in historical perspective, the dissertation locates the crux of the Burundian tragedy in the emergence of ethnicised discourses on security. Incidentally, the interpretative analysis reveals a convergence in the subject matter of African Studies and International Security Studies that presents a promising potential for further research. The explorative approach of this dissertation may be of interest to scholars in Conflict Studies, African Studies, International Security Studies, Political Science, and anyone fascinated by the small African country.